A "crisis of whiteness" in the "Heart of Darkness" : racism and the Congo Reform movement - Lösing, Felix, 1983- (Cultures of society (Bielefeld, Germany), 2020)
The British and US-American Congo Reform Movement (ca. 1890-1913) has been praised extensively for its "heroic" confrontation of colonial atrocities in the Congo Free State. Its commitment to white supremacy and colonial domination, however, continues to be overlooked, denied, or trivialised. This historical-sociological study argues that racism was the ideological cornerstone and main agenda of this first major human rights campaign of the 20th century. Through a thorough analysis of contemporary sources, Felix Lösing unmasks the colonial and racist formation of the modern human rights discourse and investigates the »historical work« of racism at a crossroads between imperial power and white crisis.--